Experimental and theoretical study of hydroxyquinolines: hydroxyl group position dependent dipole moment and charge-separation in the photoexcited state leading to fluorescence. (17th November 2016) - Mehata, Mohan Singh; Singh, Ajay K; Sinha, Ravindra Kumar
Abstract: Optical absorption and fluorescence (FL) spectra of 2-, 6-, 7-, 8-hydroxyquinolines (2-, 6-, 7- and 8-HQs) have been measured at room temperature in the wide range of solvents of different polarities, dielectric constant and refractive index. The ground state dipole moment ( µ g ) and excited state dipole moment ( µ e ) of 2-, 6-, 7- and 8-HQs were obtained using solvatochromic shift (SS) methods and microscopic solvent polarity parameters (MSPP). Change in the dipole moment (Δ µ ) between the ground and photo-excited states was estimated from SS and MSPP methods. DFT and TDDFT based theoretical calculations were performed for the ground and excited states dipole moments, and for vertical transitions. A significant enhancement in the excited state dipole moment was observed following photo-excitation. The large value of Δ µ clearly indicates to the charge-separation in the photo-excited states, which in turn depends on the position of the hydroxyl group in the ring.